The Influence of Principal Leadership, Organizational Culture, Teacher Competence, and Work Motivation on the Performance of Private Vocational School Teachers in Bekasi Regency - Alisanda, Saga Cindai; Maswanto, Maswanto; Hasanah, Hasanah (Dinasti Publisher, 2026)
This research is motivated by the importance of teachers as key actors in determining the quality of education, particularly in private Vocational High Schools (SMK), which are characterized by competency-based learning and the need for direct connections to the industrial world. In Bekasi Regency, as one of the largest industrial areas in Indonesia, private vocational schools are expected to produce competent, adaptive, and work-ready graduates. However, various indicators indicate that the performance of private vocational school teachers in Bekasi Regency is still suboptimal. This condition is reflected in student learning outcomes, readiness for skills competency tests, and the gap in quality between private and public vocational schools. This low teacher performance cannot be separated from various interrelated managerial and individual factors, so a comprehensive empirical study is needed to identify the determining factors. Theoretically and empirically, teacher performance is influenced by a combination of leadership factors, the organizational environment, professional capacity, and individual psychological conditions. In the context of educational management, the principal's leadership plays a strategic role in directing, motivating, and empowering teachers to perform optimally in accordance with the school's vision and mission. Furthermore, a strong and positive school organizational culture is believed to foster a strong work ethic, loyalty, and commitment to the institution. Furthermore, teacher competencies, including pedagogical, professional, social, and personality competencies, are key prerequisites for an effective learning process. Work motivation also serves as an internal driver that determines the level of enthusiasm, dedication, and responsibility of teachers in carrying out their professional duties. An imbalance in any of these factors has the potential to reduce teacher performance and impact the quality of vocational school graduates. Based on these problems, this study aims to analyze and empirically test the influence of principal leadership, organizational culture, teacher competency, and work motivation on the performance of private vocational high school teachers in Bekasi Regency, both partially and simultaneously. This study also aims to develop a comprehensive and contextual conceptual model of teacher performance management in accordance with the characteristics of vocational education. Thus, the results of this study are expected to not only provide theoretical contributions to the development of educational management science, but also provide practical recommendations for policymakers, principals, and educational foundation managers. This study uses a quantitative approach with an explanatory research type, which aims to explain the causal relationship between the research variables. The independent variables in this study include principal leadership, organizational culture, teacher competence, and work motivation, while the dependent variable is teacher performance. The study population was all private vocational high school teachers in Bekasi Regency, with the sample determined using a sampling technique adjusted to the population characteristics and the needs of statistical analysis. Data were collected through a closed questionnaire using a Likert scale that has been tested for validity and reliability. Data analysis was carried out using multiple linear regression or Structural Equation Modeling (SEM) based on Partial Least Square (PLS), to obtain an accurate picture of the strength and direction of influence between variables. The expected outcome of this study is empirical evidence that principal leadership significantly influences teacher performance, both directly and through the creation of a conducive work climate and organizational culture. Effective leadership, particularly transformational, instructional, and participatory leadership, is believed to be able to increase teacher work motivation, strengthen professional commitment, and encourage continuous competency improvement. A positive organizational culture is expected to play a role in building the values ​​of cooperation, responsibility, and innovation, which ultimately lead to improved teacher performance. Teacher competency is expected to have a direct influence on learning effectiveness, while work motivation functions as an internal driver that strengthens the implementation of these competencies in daily teaching practice. Theoretically, this research is expected to enrich the body of knowledge in educational management, particularly in developing human resource management models in vocational schools. This research integrates the variables of leadership, organizational culture, competency, and work motivation into a coherent conceptual framework to explain teacher performance. The research findings are expected to serve as a reference for future research examining educator performance using a multidimensional, local context-based approach. Practically, the results of this study are expected to provide strategic implications for principals and managers of private vocational schools in designing policies to improve teacher performance. Principals can use the results of this study as a basis for developing a more participatory leadership style oriented toward teacher professional development. Foundations and education offices can utilize the findings of this study to formulate competency development programs, reward systems, and strengthen sustainable school organizational culture. Thus, improving teacher performance is not solely seen as an individual responsibility, but as the result of a synergy between managerial policies, the organizational environment, and personal motivation. Ultimately, this research is expected to make a tangible contribution to improving the quality of vocational education in Bekasi Regency. By improving the performance of private vocational school teachers, the quality of the learning process is expected to improve, become more relevant to the needs of the industrial world, and produce competent and highly competitive graduates. This aligns with the national education development goal of preparing superior, professional human resources ready to face global challenges.